Mendorong Perbaikan Kebijakan Pemerintah Daerah untuk Meningkatkan Penanaman Modal Asing Langsung di Provinsi Jawa Barat - Rizki Zakariya (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
West Java Province is the region with the highest investment in Indonesia, with a growth rate of 27% during 2020-2022. Adequate infrastructure, competent human resources, and the presence of economic zones support high investment in West Java. However, local policies to stimulate investment growth are not yet optimal. West Java Regional Regulation No. 21 of 2011 on Investment has fallen behind current regulations such as the Job Creation Law, the HPKD Law, and the HPP Law. Therefore, this research aims to identify the issues of foreign investment policy in West Java and propose improvement measures. The research method employed is qualitative, utilizing legal, literature, and comparative approaches. The findings indicate that the issues of foreign investment policy in West Java include the ambiguity of incentives and facilitation provided to investors, the need for expanding the forms of incentives and facilitation, as well as weaknesses in institutional development and investment supervision. Additionally, the infrastructure in West Java Province is inadequate. Hence, it is recommended to revise the West Java Regional Regulation on Investment to ensure sustained growth of investment in the region.